Behavioral Determinants of FOMO-Driven Investments: The Mediating Role of Literacy and Self-Control - Rita Sarlawa; Sunaryo Neneng (Jurnal Locus Penelitian dan Pengabdian, 2026)
Investment decision-making behavior among Credit Union (CU) members increasingly reflects emotional, social, and cognitive interactions. This study investigates how Fear of Missing Out (FOMO), Social Influence (SI), and Risk Perception (RP) impact members’ Investment Decisions (ID), and the mediating roles of Financial Literacy (FL) and Self-Control (SC). A quantitative approach was used, collecting survey data from 300 CU members in Central Kalimantan, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that FOMO negatively affects FL and SC, while SI positively influences both mediators. Consequently, FL and SC significantly improve the quality of investment decisions, confirming their dual mediating roles. RP, however, shows no direct or indirect effect.  In conclusion, emotional and social factors shape investment decisions primarily through cognitive (financial literacy) and self-regulatory (self-control) mechanisms, rather than directly. Therefore, Credit Unions should prioritize “anti-FOMO” education and self-control development programs to foster more rational and sustainable investment behavior among members. The study contributes to behavioral finance literature by integrating cognitive and regulatory mechanisms in community-based financial settings. It offers practical guidance for Credit Unions through “anti-FOMO” education and self-control development programs.